(untitled) (Daffodil International University Journal of Science and Technology, 2011)
Abstract: The relationship between textural properties of selected Nigeria rocks and penetration rate of top-hole hammer drill was investigated. These rock samples were tested in the laboratory for mineral composition, silica content and porosity. Also, average grain size and packing density were determined from photomicrograph of the samples using empirical equations proposed by researchers. Penetration rate for each rock samples obtained in the field were correlated with the textural properties to establish their relationships. The results show that all textural character and penetration rate have high coefficient of correlation for all the samples. The highest penetration rate was experience on biotite hornblende-granite having mean packing density of 92.58% and the silica content vary for 82.60 - 82.72%. This has revealed that penetration rate of rock drill bit in quarries is related to textural rock properties and this will be necessary to have overview of time of drilling as well as rock response to mechanical loading. Keywords: Textural properties; rocks; packing density; penetration rate; top-hole-hammer drill; quarry